2011
DOI: 10.1590/s0102-67202011000200016
|View full text |Cite
|
Sign up to set email alerts
|

Características construtivas e funcionais das agulhas de radiofrequência bipolares resfriadas para reduzir o sangramento nas ressecções hepáticas

Abstract: RACIONAL: Para diminuir o sangramento em ressecções hepáticas diversas opções tecnológicas têm sido divulgadas, dentre elas a radiofrequência. A intenção dos vários métodos é evitar o clampeamento vascular, fazer menor dissecção hepática e obter menor sangramento. OBJETIVO: Apresentar uma nova técnica de agulhas paralelas de radiofrequência bipolar desenvolvidas pelos próprios autores e os detalhes técnicos de seu uso. MÉTODOS: O sistema de agulhas apresenta dois eletrodos paralelos (18 gauge cada) de 25 cm de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Among the cutting-edge technologies, is highlighting the use of RF as well known in the therapeutic armamentarium ablation of liver lesions 3,4,11,12,21 . Recent studies have shown 3,13,14,22,25 hepatectomies performed using the monopolar RF, where the blood loss and the occurrence of fistula bile was almost nil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the cutting-edge technologies, is highlighting the use of RF as well known in the therapeutic armamentarium ablation of liver lesions 3,4,11,12,21 . Recent studies have shown 3,13,14,22,25 hepatectomies performed using the monopolar RF, where the blood loss and the occurrence of fistula bile was almost nil.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the RF ablation of tumors has allowed patients with low functional reserve had controlled their lesions, leading to waiting for transplantation in patients with primary tumors 4,11,12 , or allowing an increase in its survival in cases of metastatic lesions 21 . However, despite the appropriate use of RF ablation, local recurrence at the site of ablation varies around 40% 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation